Online Game, Addiction and Learning Achievement of Senior High School Students in Jakarta - Anggraeni, Lina Dewi; Wihardja, Hany (Indonesian Journal of Disability Studies, 2020)
Online game problems being a global concern because of the risk of having a negative impact in school-age children. Game online addiction is the excessive use of computers or video games due to urges that cause social or emotional problems. This research aims to identify the relationship between online game problems and learning achievement in senior high school students in Jakarta. This research is a quantitative study with a Cross-Sectional approach. The sampling method uses a technique of purposive sampling. The number of respondents in this study was 95 senior high school students at x public school, Central of Jakarta. The result of the bivariate analysis showed that there was no significant relationship between online gaming problems and learning achievement of a high school students in Jakarta (p-value = 0.242). The implication of this research shows that online gaming problems are not the only factor that can affect the learning achievement of high school children. The other factors that are likely to influence children's learning achievement include self-motivation, family social support, and the school social environment. Recommendation for parents to supervise their children in using gadgets and the school can strengthen the rules for using gadgets in schools.